Effects of thermoneutral water, cold-water and contrasting water temperature immersions on lower limb vein cross-section - Beliard, S.; Menetrier, A.; Ravier, G.; Rakobowchuk, M.; Mourot, L.; Tordi, N. (Science & Sports, 2017)
Objectives: Immersion is often used within the framework of post-exercise recovery. Vascular effects connected to immersion are not all understood. In this study we examined the changes in common femoral vein and great saphenous vein cross-section during thermoneutral, cold, and contrasting (cold followed by hot) water immersion. Methods: Ten professional handball players visited the laboratory on three occasions. At each visit, they completed a 20-minutes procedure in an upright position: 4-minutes in air (baseline) and then 16-minutes of lower limbs thermoneutral (~35 °C), cold (~12 °C) or contrasting (2:2 minutes [~12 °C to ~35 °C] ratio) water temperature immersion, in a random order. Common femoral vein and great saphenous vein cross-sections were evaluated using echo Doppler at baseline and at the end of the 16 minute immersion period under each condition. Results: Common femoral vein cross-section was significantly increased after 16 minutes of immersion after each condition (+20.6% with thermoneutral, +14% with contrast and +7% with cold-water immersion, main effect for time P < 0.05). At the great saphenous vein, there was a significant enlargement (+13%, P <; 0.05) with thermoneutral water immersion, no difference (+1.4%, P < 0.05) during contrasting water temperature immersion and a significant decrease (-19%, P <; 0.05) after 16 minutes of cold-water immersion. Conclusion: Hydrostatic pressure, which is the same in the three immersion conditions, leads to an increase of the common femoral vein (deep venous system) cross-section no matter the water temperature. Conversely, the changes in great saphenous vein cross-section (superficial venous system) appear related to water temperature variations. This is probably related to thermoregulation mechanisms, which induce modifications in skin blood flow.